Identitas dan Keragaman Genetik Begomovirus yang Berasosiasi dengan Penyakit Keriting pada Tomat Berdasarkan Teknik Polymerase Chain Reaction (PCR)- Restriction Fragment Length Polymorphism (RFLP) - Tri Joko Santoso; Sri H. Hidayat; M. Herman; H. Aswidinnoor; Sudarsono Sudarsono (Jurnal AgroBiogen, 2008)
Begomoviruses, members of the Geminivirus,are considered as emerging plant viruses. This was due tothe increasing incidences and severities of the diseases in anumber of economically important crops, including tomato.Genetic diversities of the Begomovirus isolates infectingtomato (Lycopersicon esculentum) of several areas in Indonesiawere analyzed by using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP)technique. A 1500 base pairs of PCR fragments amplified byusing degenerate primers for Begomovirus was digestedusing four restriction enzymes, i.e., DraI, EcoRI, RsaI, andPstI. The pattern of RE digested fragments of 8 Begomovirusisolates and the predicted RFLP fragments of the Begomovirusisolates in the GeneBank database were used to determinethe genetic identities and diversities among the isolates.Positive results of the PCR amplifications proved thatdiseased tomato plant samples collected from 8 locations inJava and Sumatra were infected with at least one Begomovirusisolate. The PCR amplification products, which weredigested using the four restriction enzymes indicated thepresence of polimorfisms among the DNA fragments of theBegomovirus isolates. Identifications of the Begomovirusindicated that the Brastagi, Bogor, Sragen, Ketep, and Boyolaliisolates were Tomato Leaf Curl Virus (ToLCV); theisolates from Malang and Blitar isolates were AgeratumYellow Vein Virus (AYVV), while one isolate from Kaliurangwas Tomato Yellow Leaf Curl Virus (TYLCV). Results of thephylogenetic analysis of the 8 Begomovirus isolates basedon Begomoviruses from the DNA database indicated thatthey belonged to three different groups.